Characterization of filter performance under low-pressure operation. Issue 5 (3rd May 2016) - He, Meilu; Dhaniyala, Suresh; Wagner, Matthew
ABSTRACT: Particulate gas filters are a critical element in the purification systems used to ensure defect-free manufacturing in semiconductor industry. In atomic layer deposition (ALD) processes, these filters are typically operated under sub-atmospheric pressure conditions, but their filtration characteristics are, often, only known at atmospheric pressure. In this study, performance of a metal filter that is typically used in low-pressure ALD precursor delivery systems is studied experimentally and theoretically down to 4.5 kPa. The experimental procedure was designed to minimize the presence of multiply charged particles in the test aerosol for different operating pressures and flowrates. The experimental results suggest that most penetrating particle size only slightly varies with pressure, but the shape of the penetration curve and the maximum value of the penetration changes significantly with pressure. The experimental data are used to test predictions of filter performance at low pressures made using classical theory. The comparison results suggest that the combination of classical theory and manufacturer-specified parameters results in large errors in calculated penetration values at low pressures. Accurate predictions are seen to be possible for particle Stokes numbers less than 0.1, when an inhomogenous filtration model is used in combination with effective filter parameters that are obtained from experimental measurements of filter efficiency and pressure drop at atmospheric pressures. Copyright © 2016 American Association for Aerosol Research